2017
DOI: 10.1007/s12325-017-0618-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy Choice Is Associated with 2-Year Mortality for Patients with Heart Failure and Reduced Ejection Fraction

Abstract: Novartis Pharmaceuticals Corp. located in East Hanover, NJ, USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A real‐world study comprising 14 359 patients with HFrEF reported that the 2 year mortality rate was 27.9%. Compared with patients with monotherapy, patients with triple therapy had a 29.3% lower risk of 2 year mortality and patients who were not receiving any HF medications had the highest all‐cause mortality 21 . The MAHLER survey demonstrated that perfect adherence to HF guidelines as determined by the global adherence indicator was a strong and independent predictor of delayed hospitalization in patients with chronic HF 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A real‐world study comprising 14 359 patients with HFrEF reported that the 2 year mortality rate was 27.9%. Compared with patients with monotherapy, patients with triple therapy had a 29.3% lower risk of 2 year mortality and patients who were not receiving any HF medications had the highest all‐cause mortality 21 . The MAHLER survey demonstrated that perfect adherence to HF guidelines as determined by the global adherence indicator was a strong and independent predictor of delayed hospitalization in patients with chronic HF 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with patients with monotherapy, patients with triple therapy had a 29.3% lower risk of 2 year mortality and patients who were not receiving any HF medications had the highest all‐cause mortality. 21 The MAHLER survey demonstrated that perfect adherence to HF guidelines as determined by the global adherence indicator was a strong and independent predictor of delayed hospitalization in patients with chronic HF. 22 Another international registry focusing on the physicians' guideline adherence and prognosis in outpatients with HFrEF reported that good adherence to GDMT is associated with better clinical outcomes during 6 months of follow‐up.…”
Section: Discussionmentioning
confidence: 99%